2020
DOI: 10.3897/zookeys.992.57028
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the foraging behavior and activity patterns of the Korean wood mouse, Apodemus peninsulae, in China, using infra-red cameras

Abstract: Apodemus peninsulae, a dominant rodent species in temperature forests of northeastern China, is a model animal to explore the ecological functions of reciprocal coevolution of animals and plants. From August to October 2016, 24 infra-red cameras were installed to study the feeding behavior and activity patterns of A. peninsulae in its natural environment. By analyzing 5618 video records, we found that feeding behavior, followed by motor and sentinel behaviors, was their main activity. In the behavior spectra, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Some studies have shown that feeding and hoarding behavior of rodents had significant seasonal differences and were seen as an adaptation strategy in response to seasonal changes in food and the environment in Northeast China ( Li et al 2020 ). Our results about survival curves, consumption time, MRT , removal time and fate of seeds also indicated that the hoarding strategies of rodents varied substantially between seasons.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies have shown that feeding and hoarding behavior of rodents had significant seasonal differences and were seen as an adaptation strategy in response to seasonal changes in food and the environment in Northeast China ( Li et al 2020 ). Our results about survival curves, consumption time, MRT , removal time and fate of seeds also indicated that the hoarding strategies of rodents varied substantially between seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier results indicated that environment temperature has an important effect on changes in the activity behavior in rodents, with rodent species adjusting their foraging times and activities in response to changes in temperature ( Corp et al 1997 ; Li et al 2020 ). The temperature is similar in the spring (April–May, 1–21°C) and autumn (September–October, 0–21°C) in the research area in 2018.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations